Dual thermal stabilizing effects of xanthan gums via glycosylation and hydrogen bonding and in vivo human bioavailability of desmopressin in orodispersible film - Gil, Myung Chul; Park, Su Jun; Lee, Bong Sang; Park, Chulhun; Lee, Beom Jin (International Journal of Pharmaceutics, 2023)
Desmopressin acetate (DDAVP), a nonapeptide drug, is easily destroyed by heat in the manufacturing process of orodispersible film (ODF). A new challenging study was conducted to improve thermal stability through glycosylation and hydrogen bonding using carbohydrate gums (agar, arabic gum, carrageenan, xanthan gum) using the solvent casting method. Among gum types, xanthan gum strongly showed dual stabilizing effects of DDAVP via covalent glycosylation and hydrogen bonding, minimizing total impurities and optimizing physicochemical properties of ODF under accelerated conditions for six months. The optimized ODF formulation (O-DDAVP ODF) at a DDAVP and xanthan gum ratio of 1:1.5 had a pharmaceutically equivalent dissolution profile as compared with a commercial 0.2 mg commercial Minirin® tablet in four different media: pH 1.2, pH 4.0, and pH 6.8 buffers and deionized water. Furthermore, O-DDAVP ODF showed in vivo bioequivalence to Minirin® tablets in healthy human volunteers. Glycosylation-oriented stabilization of peptide drug using pharmaceutically active excipients against thermal denaturation could be challenged to design patient-friendly ODF.
Keywords: Administration, Oral; Biological Availability; Deamino Arginine Vasopressin; Excipients; Glycosylation; Humans; Hydrogen Bonding; Solubility; Tablets; Desmopressin acetate; Glycosylation-oriented stabilization; Hydrogen bonding; In vitro dissolution; In vivo bioequivalence; Orodispersible films; Xanthan gum